Peran Karakteristik Individu Pada Peningkatan Kinerja Karyawan - Tri Hadi Afriliyani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to explore the role of individual characteristics, including motivation, personality, competence, and work attitude, in enhancing employee performance within organizational settings. Utilizing a literature review approach, this research analyzes various previous studies and literature that demonstrate how positive individual characteristics significantly contribute to work effectiveness and productivity. The findings indicate that employees with high motivation tend to be more proactive and committed, while adaptive personality traits and adequate skills enhance their ability to complete tasks effectively. Furthermore, a positive work attitude plays a crucial role in creating a conducive work environment, which in turn can reduce turnover rates and increase employee loyalty. The implications of this research provide insights for human resource management in designing more effective employee development strategies, thereby maximizing individual potential and achieving organizational goals as a whole.